Le désert des héros : récits de vies solitaires dans les séries américaines de fiction - Joseph Belletante (Conserveries Mémorielles)
For the last twenty years, American television series have left aside the topic of adventure in the sense of evasion in order to produce a new kind of hero. The modern day hero is the mirror image of the modern individual who acts and thinks in an endless present tense, poisoned by an “evil” that keeps him from moving forward. In a post-critic perspective, this article offers a portrait of human “states of mind” that will restitute the spectator his symbolic autonomy, through singular solitudes or the loneliness of a group as is shown by four television series that are no longer in production (Friends, The Sopranos, The West Wing and Ally McBeal) in order to allow a global interpretation and that correspond to the main genres of fiction broadcasted by the American network (comedy, drama, and dramedy).